Classical feedback control with MATLAB and Simulink - Lurie, B. J.; Enright, Paul J.; Lurie, B. J. (Boca Raton, FL : CRC Press, 2012)
'This second edition textbook describes the design and implementation of high-performance feedback controllers for engineering systems. It emphasizes the frequency-domain design and methods based on Bode integrals, loop shaping, and nonlinear dynamic compensation. The authors include many problems and offer practical applications, illustrations, and plots with MATLAB simulation and design examples. This text contains homework problems accompanied by actual solutions. Examples include case studies and real-world situations'--
Rev. ed. of: Classical feedback control with MATLAB / Bois J. Lurie, Paul J. Enright. 2000.
Includes bibliographical references and index.
Keywords: MATLAB; SIMULINK; Feedback control systems